(untitled) (k:ON - Kölner Online Journal für Lehrer*innenbildung, 2025)
In German didactics, computer games are already being discussed for use in lessons. The article differentiates the field for the didactic use of casual games/mobile games in German lessons for German computer game didactics. The focus is on free-to-play mobile games (F2P) with pay-to-win computer game mechanics (P2W). These free games are strategically designed with game mechanics so that they should not end and, at certain levels, require real money for faster and/or easier progress. The mechanics thus have a strategic effect on the narrative in order to (economically) bind the players. Using a ludology-oriented structural model, two tried-and-tested integrative didactic teaching concepts are presented using the example of in-game currencies and loot boxes. Loot boxes are a kind of digital grab bag that are controlled by an algorithm to obtain items or similar in-game content. You are paid through in-game currencies. The overall focus of the article is on the integrative connection between integrative-didactic and media-reflective learning in order to holistically perspective the development of media participatory in competency-oriented German lessons.